'Pharmatrash' in South Africa: A Contemporary History of Democracy's Detritus. Issue 4 (2nd October 2019) - Hodes, Rebecca
ABSTRACT: This study examines what happens to pharmaceutical products after they have been provided, purchased, consumed and discarded. Based on an archive of medical materials, constituted over three years of collecting waste in public sites around South Africa's Eastern Cape, I analyse the uses of these products in relation to two key developments in post-apartheid history: new forms of healthcare provision and consumption; and the diversity of formal, adaptive and illicit uses of pharmaceuticals. I highlight the example of the opioid analgesic – codeine – among the most accessible and widely abused pain-killers in South Africa's pharmaceutical compendium. Through comparing local instances of codeine abuse, I draw historical connections between current and past uses of proprietary ('over-the-counter') medicines. The 'pharmatrash' in this study is the product of global developments: modern scientific research, its technological and commercial applications, and the expansion of the pharmaceutical market in the twentieth century. These materials are also resonant of national developments: the democratisation of healthcare, the burden of communicable and non-communicable diseases, and patterns of material acquisition and consumption. This article explores the social and political meanings of this 'detritus of democracy' in contemporary South Africa.